2008
DOI: 10.1038/onc.2008.326
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Src tyrosine kinase reverts chemoresistance toward 5-fluorouracil in human pancreatic carcinoma cells: an involvement of epidermal growth factor receptor signaling

Abstract: Resistance to chemotherapy is believed to be a major cause of treatment failure in pancreatic cancer. Thus, it is necessary to explore alternative therapeutic modalities to overcome drug resistance in pancreatic cancer treatment. We tested the hypothesis that Src tyrosine kinase inhibition could augment the chemosensitivity of 5-fluorouracil (5-FU)-resistant human pancreatic cancer cells to 5-FU. As detected by MTT proliferation assay, propidium iodide and annexin V staining, a combination of 5-FU þ Src kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 42 publications
4
63
0
1
Order By: Relevance
“…4B-D). Previously, it was reported that Src inhibition reverts chemoresistance to 5-FU through thymidylate synthase regulation, and the effect of Src kinase inhibition on 5-FU chemosensitivity might be accomplished by blocking 5-FU-induced EGFR-AKT activation (39). Therefore, we tested to see if the synergy between saracatinib and 5-FU observed in our study might have resulted from thymidylate synthase downregulation.…”
Section: Discussionmentioning
confidence: 94%
“…4B-D). Previously, it was reported that Src inhibition reverts chemoresistance to 5-FU through thymidylate synthase regulation, and the effect of Src kinase inhibition on 5-FU chemosensitivity might be accomplished by blocking 5-FU-induced EGFR-AKT activation (39). Therefore, we tested to see if the synergy between saracatinib and 5-FU observed in our study might have resulted from thymidylate synthase downregulation.…”
Section: Discussionmentioning
confidence: 94%
“…Src kinase inhibition by means of RNA interference or specific drugs has already been shown to enhance in vitro toxicity of cancer cells to different agents (28,29), and although in the present article, for most of the responsive cell lines, the effects of the cisplatin/dasatinib combinations seemed to be additive rather than synergistic (Fig. 2), further studies both in vitro and in vivo should be addressed to clarify the nature of the interaction between these two drugs in NSCLC, similar to what recently reported in colorectal cancer model (30).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, overexpression of activated c-Src has been reported to stimulate migration, downregulation of E-cadherin (6), and an increase in IL-8 expression and angiogenesis (7). Pharmacologic Src inhibition demonstrated significant antitumor and antimetastatic activity in an orthotopic mouse model of human PDAC (8) and reverted inherent and acquired chemoresistance in pancreatic tumor cells in vitro (9,10) and in vivo (10).…”
Section: Introductionmentioning
confidence: 99%